Characterization of recombinant desulfovibrio gigas ferredoxin - Rodrigues, Pedro (2014)
Dg ferredoxin gene was cloned using the polymerase chain reaction (PCR), inserted into vector pT7-7, and overexpressed in Escherichia coli (E. coli) grown in aerobic media. The recombinant protein is a dimer and contains a [3Fe–4S] cluster per monomer. EPR and 1H NMR data of recombinant and wild-type protein are compared.